Kepastian Hukum Permohonan Eksekusi Bangunan yang Berdiri di Atas Tanah Hak Pengelolaan Pemerintah Kota - Ula, Suchufiel; Santoso, Budi (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2021)
This study aimed to analyze the authority of the fiduciary beneficiary creditor whose object was a building that stands on the land of management rights over city government and legal certainty of loan repayment if the debtor defaults on the fiduciary guarantee. This study used a conceptual and legal approach with a normative juridical type of research. The study results indicated that the authority of the fiduciary beneficiary creditor, whose object was a building that stands on land with the management rights of the city government, was to extend it if the term of the land use permit had expired. The creditor had the right to execute or sell the object of the fiduciary guarantee on the creditor's power if the debtor could not fulfill his obligations. When the debtor defaults, legal certainty for creditors receiving fiduciary guarantees to recover their receivables were applied for execution through a district court based on the executorial title contained in the fiduciary guarantee certificate.